(untitled) (CIPEEX, 2025)
The use of 3D models in the study of medicine emerged shortly after a profound paradigm shift in medical education, whose ultimate goal was for students to be the protagonists of their own learning, with more emphasis on practical activities and the use of technology to further stimulate student contact with active learning. This study evaluated the efficiency of using 3D printed parts in Human Anatomy classes in the third semester of the Medicine course in Anápolis, Goiás. The parts were produced and used in an activity to identify the structures of the Willis polygon, and a questionnaire was administered about the parts worked on in class. The analysis of the questionnaires administered before and after the activity indicated a significant improvement in the students’ identification of the structures of the Willis polygon. The use of 3D models increased the average number of correct answers, demonstrating a positive impact on learning, facilitating the visualization, memorization, and understanding of anatomical structures, and highlighting the effectiveness of this tool in teaching.